Changes and Clarifications in the Eighth Edition of the AJCC Cancer Staging System for Breast Cancer. Issue 3 (May 2018) - Sanders, Mary Ann; Wong, Stephanie M.; Iorgulescu, Julian Bryan; Lester, Susan C.
Abstract : Abstract: In the eighth edition of the American Joint Committee on Cancer staging system for breast cancer, the definitions for T (tumor), N (nodes), and M (metastases) remain substantially unchanged but with clarifications for certain categories that may have been problematic for pathologists and clinicians. The principal change is the decision to exclude lobular carcinoma in situ from T classification. In contrast, there is a major change in how stage is determined by introducing a new clinical prognostic stage and a new pathological prognostic stage. These prognostic stages incorporate information about grade, estrogen receptor expression, progesterone receptor expression, human epidermal growth factor receptor 2 expression, and, in some cases, the Oncotype Dx Recurrence Score, in addition to T, N, and M, to create groups of cancers predicted to have a similar survival at 3 years based on information from the National Cancer Database. This review highlights the changes and notable clarifications to the TNM system and how these relate to standard pathology reporting.